Characterization of Human Vaginal Mucosa Cells for Autologous In Vitro Cultured Vaginal Tissue Transplantation in Patients with MRKH Syndrome. (5th August 2014) - Nodale, Cristina; Vescarelli, Enrica; D'Amici, Sirio; Maffucci, Diana; Ceccarelli, Simona; Monti, Marco; Benedetti Panici, Pierluigi; Romano, Ferdinando; Angeloni, Antonio; Marchese, Cinzia
Abstract : Mayer-Rokitansky-Küster-Hauser (MRKH) is a rare syndrome characterized by congenital aplasia of the uterus and vagina. The most common procedure used for surgical reconstruction of the neovagina is the McIndoe vaginoplasty, which consists in creation of a vaginal canal covered with a full-thickness skin graft. Here we characterized the autologous in vitro cultured vaginal tissue proposed as alternative material in our developed modified McIndoe vaginoplasty in order to underlie its importance in autologous total vaginal replacement. To this aim human vaginal mucosa cells (HVMs) were isolated from vaginal mucosa of patients affected by MRKH syndrome and characterized with respect to growth kinetics, morphology, PAS staining, and expression of specific epithelial markers by immunofluorescence, Western blot, and qRT-PCR analyses. The presence of specific epithelial markers along with the morphology and the presence of mucified cells demonstrated the epithelial nature of HMVs, important for an efficient epithelialization of the neovagina walls and for creating a functional vaginal cavity. Moreover, these cells presented characteristics of effective proliferation as demonstrated by growth kinetics assay. Therefore, the autologous in vitro cultured vaginal tissue might represent a highly promising and valid material for McIndoe vaginoplasty.